Estudo das atividades das cabenegrinas A-I e A-II frente aos efeitos hematológicos e histológicos induzidos pelo veneno total e frações da serpente Bothrops neuwiedi em camundongos Swiss - Arruda, Alcínia Braga de Lima (2011)
The venom of the Bothrops neuwiedi provokes an action mainly of the hemorrhagic, proteolytic and coagulant type. When inoculated, the venom cause primarily a local action, and secondarily a systemic action. The systemic effects of poisoning include changes in various systems such as hematological, cardiovascular, liver, urinary, respiratory, immune, digestive and nervous. The mechanisms that cause the changes are complex and the various toxic components of the venom may act directly or indirectly on the cells. This study aimed first to investigate possible histological and hematological caused by the whole venom and by the phospholipase A2 and lectin C fractions from Bothrops neuwiedi snake, at 2, 4, 8, 16 and 24 hours intervals in mice, and then evaluate the cabenegrins A-I and A-II in the neutralization of the biological activities of the snake whole venom, analyzing its anti-ophidian potential for possible complementation of serum therapy. We studied the actions of the whole venom and of the phospholipase A2 and lectin C fractions on the hematological system, evaluating the hemogram, the myelogram and the splenogram, at different times. The hemogram was performed by the Sysmex-Roche blood cell counter model KX-21N; the myelogram was performed through the differential and morphological count of bone marrow cells using slides obtained after cytospin (using Cytological Centrifuge model Incibrás); and the splenogram, by quantifying and morphology of the cells in "imprint" of the spleen. After the hematological study, the kidneys, spleen, liver and heart were subjected to histological analysis. All studied parameters were analyzed by the ANOVA test and by the nonparametric Kruskal-Wallis exact test, with p<0.05. The results showed that main quantitative changes in the hematological cells, using the whole venom and the phospholipase A2 and lectin C fractions were: slight increase in erythrocytes and hematocrit, leukocytosis and thrombocytopenia, with repercussion in the peripheral blood; increase of erythroid and myeloid cells in myelogram and increase in myeloid cells in the splenogram. These changes were more evident two and four hours after the poisoning. The histological changes in the kidneys, spleen, liver and heart were characterized mainly by congestion, interstitial edema, hemorrhage, hydropicdegeneration and inflammatory process. When animals were treated with cabenegrins it was detected that these could not revert the quantitative changes of the spleen cells caused by the whole venom. However, all dilutions of cabenegrins AI and A-II were able to inhibit the thrombocytopenia and the increase of myeloid cells in the myelogram, and reverse all the histological changes found in all the studied organs. The treatment with cabenegrins also showed that the cabenegrins A-I (in the 2.5:1 dilution) and the cabenegrins A-II (in the 2.5:1 and 5:1 dilutions) neutralized the changes in the differential count, i.e., these cabenegrins decreased the number of segmented neutrophils, reflecting in the total number of neutrophils. These results suggest that the cabenegrins AI and A-II may be used in the future as an adjunctive treatment of treatment of snake accidents caused by Bothrops neuwiedi.